All Days 2012
DOI: 10.2118/151176-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Equivalent Diameter Definitions on Frictional Pressure Loss Estimation in an Annulus with Pipe Rotation

Abstract: Annular flow of non-Newtonian fluids remains a ubiquitous phenomenon in drilling operations but accurately estimating the frictional pressure loss with drill pipe rotation still poses a great challenge. Since annular frictional pressure losses increases the equivalent circulating density (ECD), it becomes imperative to accurately estimate the annular pressure loss in order to keep the ECD above the pore pressure and below the fracture gradient especially in deep offshore drilling where the pore pressure and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Escudier and Gouldson [35] demonstrated experimen tally how such Taylor vortices alter the velocity profile in the annulus. Anifowoshe and Osisanya [36] found a variation of pres sure drop prediction when using different equivalent diameter definitions. The examples shown in Figs.…”
Section: T J mentioning
confidence: 99%
“…Escudier and Gouldson [35] demonstrated experimen tally how such Taylor vortices alter the velocity profile in the annulus. Anifowoshe and Osisanya [36] found a variation of pres sure drop prediction when using different equivalent diameter definitions. The examples shown in Figs.…”
Section: T J mentioning
confidence: 99%
“…However, it is difficult to select a definition for a field application as those were developed and/or applied empirically. A comparison of multiple definitions in predicting pressure losses is presented by Anifowoshe and Osisanya [3]. Other issues that make the estimation of pressure losses in drilling holes difficult are the eccentricity and the rotational speed of inner drill pipe.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other issues that make the estimation of pressure losses in drilling holes difficult are the eccentricity and the rotational speed of inner drill pipe. Many studies have been done on the flow of non-Newtonian fluids in annuli to introduce empirical/ analytical models which allow to take these effects into account [1,[3][4][5][6][7][8][9][10]. e results of the previous studies show that the annular pressure losses for non-Newtonian (power law) fluids flowing in a drill hole depend on drill pipe rotation speed, fluid properties, flow regimes (laminar/ transitional/turbulent), diameter ratio, eccentricity, and equivalent hydrodynamic roughness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To transform annular flow to pipe flow, the effective diameter needs to be replaced the diameter parameter. Anifowoshe et al [3] found that the definition of hydraulic diameter as expressed in (3) is the appropriate estimation of pressure loss for power law fluid. Hence frictional pressure loss inside an annulus using slot equation is defined as (4)…”
Section: Mathematical Modelsmentioning
confidence: 99%